Determinación de la calidad del agua por bioindicadores (macroinvertebrados) en el Río Aláquez, cantón Latacunga, provincia de Cotopaxi, periodo 2020 – 2021. - Cedeño Santos, Angie Pierina (2021)
The industrialization of the Aláquez parish, apart from the economic development that it has generated for this area, has also contributed to the contamination of the water resource, and a need has arisen on the part of the community to know the quality of the water that is being used for water activities. irrigation, constituting a potential danger by including various pollutants of phytosanitary, organic, and inorganic origin in the trophic chain. This project is aimed at evaluating the water resource through the presence of various bioindicators such as macroinvertebrates. The methodology used to meet the proposed objective was to calculate the indices such as: BMWP / col, ABI, EPT, ICA and SHANNON WEAVER, these indices take advantage of data such as the abundance of species, the families of macroinvertebrates, the physical-chemical parameters and microbiological and, the biodiversity of the individuals found in the area. To carry out a representative study, the Aláquez River micro-basin was divided into three segments; outcrop, middle channel, and mouth, for each area a sampling was made in the months of November, December, and January to compare results to establish the condition of the water resource. At the same time, it was found that the flow is related to the abundance of individuals, since the higher the flow, there is less macroinvertebrates, therefore, the biological indices with fewer families present a low score that means that the quality of the Water will be in a range of “polluted waters” such is the case of the Aláquez River, where the current state of the water is not in good condition due to anthropic activities in the area, reflecting poor solid and liquid waste management by the competent authorities of the sector. In the three months of study, a total of 2174 individuals were collected where it was determined that the quality of the river in the study areas is "Critical - Very Critical" with a diversity "Little - Medium" according to the aforementioned indices, the ICA index corroborated the information of the bioindicators by having the water quality "Good - Fair - Bad", and the physical-chemical and microbiological parameters analyzed in the laboratory for the month of November in the area of the middle channel and the mouth did not meet the conditions of dissolved Oxygen due to the presence of a large amount of organic matter that consumes this element for its biodegradation, the other parameters analyzed were in accordance with current Environmental Regulations.